A porous ionic liquid gel membrane material, a preparation method and application thereof

CN122958813APending Publication Date: 2026-10-23NATIONAL FOOD SAFETY INSPECTION & TESTING TECHNOLOGY RESEARCH CENTER (NATIONAL FOOD SAFETY HAZARD ANALYSIS & CRITICAL CONTROL POINTS APPLICATION RESEARCH CENTER)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611094189.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-22
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0005]鉴于上述现有技术的情况,本发明提供一种多孔离子液体凝胶膜材料,其通过将离子液体的结构特点用于检测材料中并发挥其特异性识别功能,以解决现有技术中缺少一种能够用于复杂样品基质中特异识别黄曲霉毒素前体物材料的技术问题

Benefits of technology

[0051]本发明的多孔液体凝胶膜材料对黄曲霉毒素前体物具有较高吸附容量、良好的选择性和分阶段式热稳定性,特别是在快速蒸发电离条件下仍能保持重复的被切割性能,能够保证非损检测发酵食品中痕量黄曲霉毒素前体物时的精准度,从而实现食品样品原位电离技术与黄曲霉毒素早期预警模式相结合的技术突破。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122958813A_ABST
    Figure CN122958813A_ABST
Patent Text Reader

Abstract

The application provides a porous ionic liquid gel membrane material and a preparation method and application thereof, the gel membrane material is a loose porous three-dimensional network structure formed by functional monomers of repeating structural units and membrane bodies, the functional monomers are ionic liquids formed by imidazole derivatives, the membrane bodies are formed by cross-linking of hydroxyethyl cellulose and sodium polyacrylate, and nitrogen positive ions formed by cross-linking ionic liquids of hydroxyethyl cellulose between the repeating structural units and oxygen negative ions formed by sodium polyacrylate are connected through electrostatic action. The material has a high adsorption capacity, good selectivity and staged thermal stability for aflatoxin precursors, especially can still maintain repeated cutting performance under the condition of rapid evaporation ionization, can ensure the accuracy when trace aflatoxin precursors in fermented food are detected without damage, and thus realizes a technical breakthrough of combining food sample in-situ ionization technology and an aflatoxin early warning mode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of macromolecular materials chemistry, and in particular to a porous ionic liquid gel membrane material, its preparation method, and its application. Background Technology

[0002] Mycotoxins pose a serious threat to human health. Among them, aflatoxins (AFs), a major mycotoxin, are highly toxic and carcinogenic metabolites mainly produced by Aspergillus flavus and Aspergillus parasiticus. They commonly contaminate grains, beans, their fermented products, and even condiments such as soy sauce, vinegar, and brewed sauces. Current AFs early warning technologies mainly rely on AFs detection technology. Once the toxin is detected, contamination has already occurred, making it difficult to meet the needs of early warning. Researchers are currently focusing on how to control AFs contamination and its hazards at the source, providing timely warnings and implementing control measures before the risk of AFs contamination occurs. However, the biosynthesis of AFs is very complex, involving multiple enzymatic steps and the accumulation of different precursor molecules. Studies have identified approximately 15 precursor substances. The synthetic pathway uses acetyl-CoA as the starting unit, followed by a series of catalytic modification processes such as oxygenation, dehydrogenation, and methyl transfer, ultimately forming highly oxidized AFs. The biosynthesis of aflatoxins (AFs) involves the early stages of polyketide compounds such as Averantin (AT) and Averufin (AF), but these compounds exhibit poor structural stability and are difficult to transport and preserve. Furthermore, trachomatin (ST) and O-methyltrachomatin (OMST) accumulate in the middle stages, laying the theoretical foundation for later early warning detection. In the later stages, AFB1, AFB2, AFG1, and AFG2 become highly oxidized and tend towards stability. Currently, the main challenges in detecting AF precursors in food lie in the interference of complex matrices, trace amounts, and structural instability. To improve the specific adsorption and recognition performance of structurally similar AFs and precursors, porous materials can provide greater adsorption capacity for adsorption extraction. Moreover, multifunctional groups can generate multiple interactions with various targets. Therefore, developing porous materials with multifunctional groups as adsorbents can achieve the extraction and enrichment of trace targets in complex samples.

[0003] Ionic liquids are typically composed of a wide variety of asymmetric organic cations (containing heteroatoms such as nitrogen) and organic or inorganic anions. Even subtle changes in the types or bonding modes of these cations and anions can lead to significant alterations in the material's physicochemical properties (viscosity, solubility, etc.) and result in different interactions between the ionic liquid and the analyte. Based on these characteristics, ionic liquids are often considered functional molecules due to their structure containing specific hydrophilic / hydrophobic groups, various hydrogen-bonding functional groups, and high charge density. This allows for multiple interactions with the analyte, such as hydrophilic / hydrophobic interactions, hydrogen bonding, and electrostatic interactions, making them promising extraction materials for sample pretreatment. This study aims to utilize the functionalized "multi-legged" functional groups of ionic liquids and the porous, three-dimensional network structure of hydrogel supports to synthesize a novel porous ionic liquid gel membrane material with specific recognition capabilities, thermochemical stability, and compatibility with rapid detection REIMS. The combination of this gel membrane material with the rapid detection technology REIMS provides crucial technical support for early warning and prevention of aerosol flammation (AFs).

[0004] Therefore, it is urgent to develop an ionic liquid gel membrane with mild adsorption and high selectivity as an extraction material to achieve highly sensitive detection of AFs precursors in complex sample matrices. Summary of the Invention

[0005] In view of the above-mentioned prior art, the present invention provides a porous ionic liquid gel membrane material, which utilizes the structural characteristics of ionic liquids in the detection material and exerts its specific recognition function to solve the technical problem of the lack of a material that can be used to specifically recognize aflatoxin precursors in complex sample matrices.

[0006] To achieve the above-mentioned objectives of this invention, the following technical solution is adopted:

[0007] One objective of this invention is to provide a porous ionic liquid gel membrane material, characterized in that it is a loose, porous three-dimensional network structure formed by functional monomers of repeating structural units and a membrane body. The functional monomers are ionic liquids formed by imidazole derivatives. The membrane body is formed by crosslinking hydroxyethyl cellulose and sodium polyacrylate, and the nitrogen cations formed by the crosslinking of hydroxyethyl cellulose and ionic liquid and the oxygen anions formed by sodium polyacrylate are connected by electrostatic interaction between the repeating structural units.

[0008] The porous ionic liquid gel membrane material has a loose and porous three-dimensional network structure (see Appendix for details). Figure 1 (The relevant structure in the image), in the X-ray powder diffraction data, crystal diffraction peaks are present at 2θ at 32° and 33°.

[0009] The porous ionic liquid gel membrane material has an average specific surface area of ​​1.25~2.52 m².2 ·g −1 The average pore size is 30~55 nm.

[0010] The porous ionic liquid gel membrane material is in a colloidal liquid state in water, and becomes a loose porous network solid state after vacuum drying. It is hydrophilic, and the contact angle range is 73~88° during surface tension testing.

[0011] Furthermore, the functional monomer is selected from one or more combinations of ionic liquids formed from the following imidazole derivatives: the imidazole derivative is 1-vinylimidazole (VL), and the ionic liquid formed from the imidazole derivative has the following structure: wherein R is C2NH6Br - C4H6Br - or C7BH8O2Br - Specifically, these are 1-vinyl-3-propylamine imidazole hydrobromide ([AVIM]Br), 1-vinyl-3-butenylimidazolium bromide ([VIM]Br), and 3-(4-boronbenzyl)-1-vinylimidazolium-3-bromide ([BVIM]Br).

[0012]

[0013] The structures of the hydroxyethyl cellulose (HEC) and the sodium polyacrylate (PAAS) are described later, and the membrane structure they form is as follows. Figure 1 As shown.

[0014] The second objective of this invention is to provide a method for preparing the above-mentioned porous ionic liquid gel membrane material, characterized by comprising the following steps: (1) preparing an imidazole derivative into an ionic liquid as a functional monomer; (2) preheating and stirring the crosslinking agent and the functional monomer prepared above, then adding hydroxyethyl cellulose (HEC) and a protic polar solvent to react and obtain a homogeneous solution, cooling to room temperature after the reaction, adding an aqueous solution of sodium polyacrylate (PAAS) of the same volume as the homogeneous solution obtained above, and repeatedly stirring and mixing to form a membrane until a large amount of powder precipitates; (3) collecting the powder and placing it on a glass plate, and obtaining the gel membrane material after processing and vacuum drying.

[0015] In step (1), the ionic liquid is prepared as follows:

[0016] The imidazole derivative, crosslinking agent, and desiccant are mechanically stirred in an organic solvent to obtain a mixture. The mixture is then heated in an oil bath under nitrogen atmosphere. After the reaction is complete, the mixture is cooled to room temperature, and the precipitate is collected or removed. The solid precipitate or the supernatant is dissolved and recrystallized or washed several times with a purification solvent. After vacuum drying, an orange-yellow viscous solid, a yellow-brown transparent liquid, or a white-gray solid can be obtained.

[0017] At this time, the crosslinking agent that reacts with the imidazole derivative is 2-bromoethylamine hydrobromide, 4-bromo-1-butene, or 4-(bromomethyl)phenylboronic acid;

[0018] The desiccant is sodium bicarbonate and anhydrous magnesium sulfate;

[0019] The organic solvent is ethanol or acetonitrile;

[0020] The impurity removal solvent is an aqueous solution of potassium hydroxide (pH 8), ethyl acetate, or acetonitrile.

[0021] Preferably, the mass ratio of the imidazole derivative to the crosslinking agent is 1:(1~3), more preferably 1:1.2~2.0;

[0022] Preferably, the heating temperature is 60~100 ℃, more preferably 70~82 ℃;

[0023] Preferably, the heating time is 12 to 36 hours, more preferably 18 to 24 hours;

[0024] Preferably, the mechanical stirring speed is 200~800 rpm, more preferably 400~600 rpm.

[0025] In step (2),

[0026] Prepared by solvent polymerization: The crosslinking agent reacting with hydroxyethyl cellulose is a halogenated hydrocarbon compound containing an epoxy structure, such as epichlorohydrin, epibromochlorohydrin, methyl epichlorohydrin, bromochlorohydrin, or 1,2-epoxy-4-chlorocyclohexane, preferably epichlorohydrin;

[0027] The aprotic solvent is dimethyl sulfoxide, N,N-dimethylformamide, or acetone, preferably dimethyl sulfoxide;

[0028] The hydroxyethyl cellulose (HEC) is a nonionic cellulose ether with the structure shown below, and its chemical formula is (C2H6O2). n The degree of polymerization n ranges from 600 to 800, preferably 750; the viscosity ranges from 700 to 5000 mPa·s (25 ℃), preferably 2300 mPa·s (25 ℃), which is a medium viscosity grade product.

[0029] The sodium polyacrylate (PAAS) is a water-soluble linear polymer with the following structure and chemical formula (C3H3O2Na). n Molecular weight ≥ 3x10 7 n ranges from 1 to 10. 6 ~5x10 6 , preferably 3 x 10 6~5 x10 6 It belongs to the medium molecular weight type of material;

[0030]

[0031] Preferably, the mass ratio of the crosslinking agent, functional monomer, and hydroxyethyl cellulose is 1:(1~3):(0.1~1), more preferably 1:(2~3):(0.2~0.5).

[0032] Preferably, the concentration of the sodium polyacrylate aqueous solution is 2~10 mg·mL⁻¹, more preferably 5 mg·mL⁻¹;

[0033] Preferably, the preheating temperature is 30~50 ℃, more preferably 40~45 ℃;

[0034] Preferably, the preheating time is 1 to 3 hours, more preferably 2 hours;

[0035] Preferably, the heating temperature is 60~100 ℃, more preferably 70~80 ℃;

[0036] Preferably, the heating time is 2 to 8 hours, and more preferably 6 hours;

[0037] Preferably, the mechanical stirring speed is 200~800 rpm, more preferably 400~600 rpm.

[0038] In step (3), the powder treatment is to place the powder on a glass plate, cover it with another glass plate and leave it overnight to form a transparent gel film. Then, the gel film is soaked in deionized water to remove impurities and dried to obtain the gel film material.

[0039] To explain, in order to ensure the robustness and flatness of the composite gel membrane material, the functional monomers of the present invention are first cross-linked with the macromolecular membrane single chain - hydroxyethyl cellulose during the above preparation and synthesis process, and then reacted with the macromolecular membrane cross-chain - sodium polyacrylate to ensure that the aforementioned functional monomers can be uniformly and stably incorporated into the cross-linked polymerized membrane structure.

[0040] A third objective of this invention is to provide the application of the porous ionic liquid gel membrane material prepared by the above-mentioned method in resisting competitive interference from aflatoxin or in preparing products for enriching aflatoxin precursors.

[0041] Preferably, the aflatoxin includes at least one of aflatoxin B1, aflatoxin B2, aflatoxin G1, or aflatoxin G2.

[0042] Preferably, the aflatoxin precursor includes at least one of Averantin (AT), Averufin (AF), trachomatis (Z), or O-methyltrachomatis (OZ).

[0043] Among them, through adsorption isotherm and adsorption kinetics experiments, the porous ionic liquid gel membrane material has an adsorption capacity of 177~195 µg·g⁻¹ for aflatoxin and its precursor, which has a high adsorption capacity; and the time for adsorption to reach equilibrium is 20~40 min, preferably 30 min.

[0044] A method for enriching aflatoxin and its precursors involves using a porous ionic liquid gel membrane material to adsorb at least one aflatoxin and its precursor. The method comprises placing the porous ionic liquid gel membrane material in a 1 mL liquid sample containing aflatoxin and its precursor for adsorption. When adsorption reaches equilibrium, the aflatoxin and its precursor are eluted with an organic solvent and then recovered and detected. The adsorption mechanism is analyzed by evaluating the differences in adsorption recovery rates of different materials.

[0045] In the above applications, when the porous ionic liquid gel membrane material adsorbs aflatoxin and its precursors, the amount of the gel membrane material used is 3-10 mg, preferably 5-6 mg, based on 1 mL of liquid sample.

[0046] Preferably, the aflatoxin and its precursors are eluted using the organic solvent diethylene glycol during extraction, and the eluting ions are potassium chloride.

[0047] Preferably, the pH of the elution solvent is 3-9, more preferably 6.5-7;

[0048] Preferably, the elution time is 30-90 min, more preferably 60 min, and the eluent volume is 1-5 mL, more preferably 1.5-2 mL.

[0049] The fourth objective of this invention is to provide a rapid detection method for aflatoxin precursors using the aforementioned porous ionic liquid gel membrane material, providing key technical support for early warning and prevention and control of aflatoxin.

[0050] Beneficial effects

[0051] The porous liquid gel membrane material of this invention has a high adsorption capacity, good selectivity and staged thermal stability for aflatoxin precursors. In particular, it can maintain repeatable cleavage performance even under rapid evaporation ionization conditions, which can ensure the accuracy of non-destructive detection of trace aflatoxin precursors in fermented foods. This achieves a technological breakthrough by combining in-situ ionization technology of food samples with an early warning mode for aflatoxin.

[0052] The porous ionic liquid gel membrane material of the present invention has a loose porous network feature, which endows the material with certain water absorption / solvent properties, and can provide a greater adsorption capacity for adsorption extraction, so that it can effectively enrich aflatoxin and precursors in the sample.

[0053] The porous ionic liquid gel membrane material provided by this invention has selective adsorption mainly related to the π electron cloud, amino or phenylboronic acidation of the imidazole ring in the functional monomer, which provides favorable conditions for hydrogen bonding, electrostatic and other interactions between aflatoxin and its precursor molecules. The adsorption mechanism of the porous ionic liquid gel membrane material of this invention for aflatoxin and its precursors is related to the following three forces: ① The imidazole structure of the ionic liquid itself has an inherent electrostatic effect, which adsorbs both aflatoxin and its precursors containing π electron clouds; ② The amino group has a higher adsorption capacity for aflatoxin and other products with a coumarin-based structure, specifically at the 1,3-diketone site, and the adsorption is achieved through hydrogen bonding, with an adsorption recovery rate as high as 91.7%~99.4%; however, the adsorption recovery rate for aflatoxin precursors is relatively low; ③ After derivatization with phenylboronic acid, the adsorption capacity for aflatoxin precursors with anthraquinone-based structures is even higher, specifically through the cis-dihydroxyl group, and the adsorption is also achieved through hydrogen bonding, with an adsorption recovery rate as high as 73.1%~99.4%; in contrast, the adsorption recovery rate for aflatoxin is relatively low. In this way, porous ionic liquid gel membranes formed by imidazole derivative ionic liquids with different functionalizations can specifically bind to different target substances and eliminate competitive interference, thus achieving differential selectivity. Therefore, these weak interactions enable the accurate non-destructive detection of target substances, especially unstable aflatoxin precursors.

[0054] Furthermore, the gel membrane material prepared by adjusting the synthesis steps in the preparation process has uniformity and flatness. The gel membrane material of the present invention has certain water absorption / solvent properties, so that when it is cut at high temperature by REIMS scalpel, it can quickly generate steam for mass spectrometry detection. This staged thermal stability avoids to some extent the impact of thermal degradation of material components on the experimental data of aflatoxin target detection. Attached Figure Description

[0055] Figure 1 This is a schematic diagram of the synthesis reaction process of the porous ionic liquid gel membrane material of the present invention;

[0056] Figure 2 The images shown are scanning electron microscope (SEM) images of the porous ionic liquid gel membrane materials provided in Embodiment 2 and the comparative example of the present invention. In the images, AD are SEM images of the GL, 2M, 1M and VL gel membranes provided in the comparative example of the present invention, respectively, and EG are SEM images of the [VIM]Br, [AVIM]Br and [BVIM]Br gel membranes provided in Embodiment 1 of the present invention, respectively.

[0057] Figure 3 The images show the contact angle surface tension measurement test diagrams of the porous ionic liquid gel membrane materials provided in Embodiment 2 and the comparative example of the present invention. In the image, A is the VL gel membrane provided in the comparative example of the present invention, and B and D are the contact angle surface tension measurement test diagrams of the [AVIM]Br, [VIM]Br and [BVIM]Br gel membranes provided in Embodiment 1 of the present invention, respectively.

[0058] Figure 4 The nitrogen adsorption-desorption isotherms of the porous ionic liquid gel membrane materials provided in Embodiment 2 and the comparative example of the present invention are shown. In this embodiment, A is the VL gel membrane provided in the comparative example of the present invention, and B and D are the nitrogen adsorption-desorption isotherms of the [AVIM]Br, [VIM]Br and [BVIM]Br gel membranes provided in Embodiment 1 of the present invention, respectively.

[0059] Figure 5 The thermogravimetric analysis diagrams of the porous ionic liquid gel membrane materials provided in Embodiment 2 and the comparative example of the present invention are shown. In this invention, A is the VL gel membrane provided in the comparative example of the present invention, and B and D are the thermogravimetric analysis diagrams of the [VIM]Br, [AVIM]Br and [BVIM]Br gel membranes provided in Embodiment 1 of the present invention, respectively.

[0060] Figure 6 The diagram shows the structural characterization of the porous ionic liquid gel membrane materials provided in Embodiment 2 and the comparative example of the present invention, wherein A is an infrared spectrum and B is an XRD diffraction pattern.

[0061] Figure 7 This is a schematic diagram of the adsorption of the porous ionic liquid gel membrane material provided in Embodiment 3 of the present invention, wherein A is a static adsorption diagram and B is a dynamic adsorption diagram;

[0062] Figure 8 This is a schematic diagram illustrating the differences in adsorption efficiency of different porous ionic liquid gel membrane materials for aflatoxin and its precursors provided in Example 4 of the present invention.

[0063] Figure 9 The extraction parameter optimization results established for the porous ionic liquid gel membrane material provided in Example 5 of the present invention are as follows: A is the optimized result of adsorbent dosage, B is the optimized result of elution solvent type, C is the optimized result of solution pH, D is the optimized result of elution ion type, E is the optimized result of elution solvent volume, and F is the optimized result of elution time.

[0064] Figure 10 This is a schematic diagram of the porous ionic liquid gel membrane material provided in Embodiment 6 of the present invention being used in conjunction with REIMS for rapid detection of food samples. Detailed Implementation

[0065] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0066] Unless otherwise defined herein, the scientific and technical terms used in conjunction with this invention shall have the meanings commonly understood by one of ordinary skill in the art. The meaning and scope of terms shall be clear; however, in any case of potential ambiguity, the definitions provided herein shall prevail over any dictionary or foreign definitions. In this application, unless otherwise stated, the use of "or" means "and / or". Furthermore, the use of the term "comprising" and other forms is non-limiting.

[0067] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0068] In this invention, the term "complex sample" refers to food.

[0069] The present invention will be explained below with reference to embodiments. Those skilled in the art will understand that the following embodiments are for illustrative purposes only and should not be considered as limiting the scope of the invention. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in the art (e.g., refer to J. Sambrook et al., *Molecular Cloning: A Laboratory Manual*, 3rd edition, Science Press, translated by Huang Peitang et al.) or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.

[0070] Example 1

[0071] The preparation method of porous ionic liquid gel membranes includes the following steps, and the schematic diagram of the synthesis reaction is shown below. Figure 1 As shown:

[0072] (1) Preparation of ionic liquids as functional monomers

[0073] (1-1) Preparation of the ionic liquid 1-vinyl-3-propylamine imidazole hydrobromide ([AVIM]Br):

[0074] The product was prepared using a simple solvothermal method. 5.65 g of 1-vinylimidazole was weighed and added to a three-necked round-bottom flask. 20 mL of ethanol was added, and the mixture was mechanically stirred at 500 rpm to dissolve. Then, 8.2 g of 2-bromoethylamine hydrobromide was weighed and dissolved in the same solution. The mixture was then heated to 80 °C under nitrogen atmosphere for 24 h. After the reaction, the ethanol was removed, and the solid residue was dissolved in a small amount of water. Solid potassium hydroxide was added to adjust the pH to 8. The product was purified by recrystallization and dried in a vacuum oven at 60 °C for 24 h to obtain an orange-yellow viscous solid (molecular formula: C7N3H). 12 Br (molecular weight: 312).

[0075] (1-2) Preparation of the ionic liquid 1-vinyl-3-butenimidazolium bromide ([VIM]Br):

[0076] The solution was prepared using a simple solvothermal method. 8.54 g of 1-vinylimidazole was weighed and added to a three-necked round-bottom flask. 20 mL of acetonitrile was added, and the mixture was mechanically stirred at 500 rpm. Then, 7.62 g of sodium bicarbonate and 15.9 g of 4-bromo-1-butene were added to the suspension. The mixture was heated to 82 °C for 24 h under nitrogen protection. After the reaction was complete, the mixture was cooled to room temperature, the precipitate was removed, and the solution was washed 5-6 times with ethyl acetate. After drying with anhydrous magnesium sulfate, the solution was filtered again. The supernatant was dried under vacuum at 40 °C to obtain a yellowish-brown transparent liquid for later use (molecular formula: C9H). 13 N2Br, molecular weight: 229.

[0077] (1-3) Preparation of the ionic liquid 3-(4-boronbenzyl)-1-vinylimidazol-3-bromine salt ([BVIM]Br):

[0078] The reaction was prepared using a simple solvothermal method. Under a nitrogen atmosphere, 3.76 g of 1-vinylimidazole and 8.66 g of 4-(bromomethyl)phenylboronic acid were weighed and added to a three-necked round-bottom flask, dissolved in 40 mL of acetonitrile, and heated to 80 °C with mechanical stirring at 500 rpm for 24 h. The resulting solid was then collected, washed three times with acetonitrile, and dried under vacuum at 60 °C to obtain a white-gray solid (molecular formula: C). 12 N2BOH 13 Br, molecular weight: 393.

[0079] (2) Porous ionic liquid gel membrane (hereinafter sometimes referred to as PILc)

[0080] The solution polymerization method was used to prepare the product: 14.24 g of epichlorohydrin was weighed and added to a three-necked round-bottom flask. The mixture was heated to 40 °C with mechanical stirring at 500 rpm. 30 g of one of the functional monomers (1-1), (1-2), or (1-3) prepared above was slowly added. The mixture was pre-reacted for 2 h. Then, the temperature was raised to 80 °C and 5 g of hydroxyethyl cellulose and 50 mL of dimethyl sulfoxide were added. The mixture was stirred for 6 h to obtain a homogeneous solution. After the reaction was completed, the mixture was cooled to room temperature. Sodium polyacrylate was prepared into an aqueous solution with a concentration of 5 mg·mL⁻¹ and added to the room temperature solution of the above reaction in an equal proportion. The mixture was stirred and mixed repeatedly. A large amount of powder was observed to precipitate.

[0081] (3) Collect the powder and place it on a glass plate. Cover it with another glass plate and leave it overnight to form a transparent gel film. Then, soak the gel film in deionized water for 3 hours to remove impurities. After vacuum drying at 30 °C, obtain the respective gel film materials 1, 2 or 3.

[0082] Comparative Example

[0083] To investigate whether different imidazole derivative binding sites can generate a porous structure of composite gel membrane, the 30 g functional monomer in Example 1 (2) was replaced with imidazole (GL) / 1-methylimidazolium (1M) / 2-methylimidazolium (2M) / 1-vinylimidazolium (VL), while the other steps remained unchanged, and PILc was synthesized as a comparison.

[0084] Example 2

[0085] Detailed characterization experiments were conducted on the PILc materials prepared in Example 1 and the comparative examples to demonstrate the successful preparation of the PILc material of the present invention and its excellent physicochemical properties. The specific details are as follows:

[0086] 1. The morphology and elemental composition of PILc were detected using scanning electron microscopy (SEM). The results are as follows: Figure 2As shown, the binding sites of imidazole derivatives were first examined. SEM images of GL, 2M, 1M and VL gel membrane materials were displayed in the AD, respectively, showing the comparative examples. It can be seen from the images that only the VL gel membrane surface has obvious pores, which is expected to form a loose porous three-dimensional network gel membrane structure. The SEM images of EG show the [VIM]Br, [AVIM]Br, and [BVIM]Br ionic liquids synthesized based on VL, and the porous ionic liquid gel membrane materials obtained by further reactions. In Figure E, the [VIM]Br material formed a layered stacked structure, where the pores were not obvious, hindering the flow between the gel and the solvent, thus resulting in a low adsorption capacity. However, the pores of [AVIM]Br in Figure F were smoother and flatter than those of VL in Figure D, and the pores were deeper, making the material resemble a fluffy sponge. This structure facilitated the direct passage of the solvent through the gel layer, improving the adsorption capacity. In Figure G, [BVIM]Br, in addition to having smooth pores, also had crystalline particles protruding from the surface, which may be related to the boric acid functionalization of the gel membrane. The prominent hydrophobic crystalline structure facilitated the affinity and specific adsorption of hydrophobic target substances such as aflatoxin precursors onto the gel membrane. The adsorption functions of the above gel membrane materials were observed in subsequent tests.

[0087] 2. Using contact angle surface tension (CA) testing to evaluate the hydrophilicity / hydrophobicity of PILc is crucial for fully realizing its performance. Figure 3 The contact angle and surface tension test graphs of the gel film materials prepared in Example 1 and Comparative Example (A) are shown. As shown in Figure A, the average contact angle of the VL gel film in Comparative Example is 73.2°; the average contact angle of the [VIM]Br gel film in Figure C is 73.8°; the average contact angle of the [AVIM]Br gel film in Figure B increases significantly to 78.6°, which may be related to the amino functionalization of the gel film; the average contact angle of the [BVIM]Br gel film in Figure D increases significantly to 87.5°. These θ values ​​are all less than 90°, indicating that they are hydrophilic materials. The contact angle results above show that the hydrophilicity comparison is VL ≈ [VIM]Br > [AVIM]Br > [BVIM]Br. This can be attributed to the phenylboronic acid functionalization of the [BVIM]Br gel film in Figure D, which significantly increases its contact angle, thereby leading to a decrease in hydrophilicity. In addition, due to the large polarity differences between AFs and their precursors, gel membrane materials need to have the properties of being both hydrophilic and hydrophobic to the target analytes, in addition to having a certain water absorption capacity. In other words, different hydrophilic / hydrophobic gel membrane materials are needed to match different AFs and precursors, thus showing great potential in enriching hydrophobic AF precursors in food samples.

[0088] 3. Figure 4The figures are nitrogen adsorption-desorption isotherms of the porous ionic liquid gel membrane materials provided in Embodiment 2 and the comparative example of the present invention, where A is the VL gel membrane provided in the comparative example of the present invention, and B and D are nitrogen adsorption-desorption isotherms of the [AVIM]Br, [VIM]Br and [BVIM]Br gel membranes provided in Embodiment 1 of the present invention, respectively. The specific explanation is as follows: The porous structure of PILc was studied by N2 adsorption-desorption measurements. In Figure A, the N2 adsorption-desorption isotherm of the VL gel membrane is not closed, with an average pore size of 48-54 nm and a specific surface area of ​​only 1.83 m²·g⁻¹. This indicates that the membrane material has a weak effect on the adsorbate, resulting in a certain degree of incomplete adsorption-desorption. As shown in Figure C, the N2 adsorption-desorption isotherm of the [VIM]Br gel membrane is closed, but the mesoporous hysteresis loop is very small, with an average pore size of 30-37 nm and a specific surface area reduced to 1.25 m²·g⁻¹. This indicates that the layer stacking of the [VIM]Br gel membrane material affects the adsorption capacity. In Figure B, the specific surface area of ​​the [AVIM]Br gel membrane increases to 2.52 m²·g⁻¹, and the mesoporous hysteresis loop increases, with an average pore size of 48-55 nm. This indicates that the material's effect on the adsorbate is enhanced. As can be seen from Figure D, [BVIM]Br The gel membrane has a specific surface area of ​​1.72 m²·g⁻¹, an average pore size of 40–47 nm, and the N₂ desorption isotherm is significantly higher than the adsorption isotherm, indicating that the [BVIM]Br gel membrane material has no strong interaction with the adsorbate, thus allowing adsorbed gas molecules to completely detach from the pores. These results demonstrate that the adsorption of the PILc gel membrane of this invention mainly relies on the weak interactions of the mesoporous structure, and such adsorption avoids the conversion loss of unstable AFs precursors during the material adsorption process.

[0089] 4. To investigate the stability of PILc materials under high-temperature conditions, the thermal stability of PILc was evaluated using thermogravimetric analysis (TG). Figure 5Thermogravimetric analysis (TG) curves of the porous ionic liquid gel membrane materials provided in Embodiment 2 and the comparative example of the present invention are shown. In Figure A, the VL gel membrane provided in the comparative example of the present invention is shown. Figures B and C are the TG curves of the [VIM]Br, [AVIM]Br, and [BVIM]Br gel membranes provided in Embodiment 1 of the present invention, respectively. The results are shown in Figures AD. The TG curves show that the weight of all four materials decreased as the temperature increased from approximately 30 °C to about 60 °C. This weight loss is related to dehydration, indicating that the PILc material itself possesses certain water absorption / solvent properties. Further heating from 60 °C resulted in only one inflection point for the weight of the VL gel membrane material in Figure A, while the weight loss of the [AVIM]Br, [VIM]Br, and [BVIM]Br gel membranes in Figures B and C all exhibited three inflection points. This indicates that the weight loss is related to the disruption of the PILc gel framework structure and the ionic liquid. The three-step thermal degradation characteristics confirm the uniform and stable structure of the PILc material. In addition, it can be shown that the PILc material of the present invention has different stages of thermal stability. This staged thermal stability avoids the influence of thermal degradation of material components on the experimental data of AFs target analytes detection to a certain extent, which is suitable for its intended application.

[0090] 5. Figure 6 The diagram illustrates the structural characterization of the porous ionic liquid gel membrane materials provided in Embodiment 2 and the comparative example of the present invention. First, Fourier transform infrared spectroscopy was used to compare the spectra of different PILc materials. Figure A shows the infrared spectrum; Figure B shows the XRD diffraction pattern. As shown in Figure A, the VL, [VIM]Br, [AVIM]Br, and [BVIM]Br gel membranes all exhibit characteristic absorption peaks at 3430-3440 cm⁻¹, which are attributed to the vibrational absorption peak of NH, representing the imidazolium group, indicating the presence of the ionic liquid as a functional monomer. The two types of absorption peaks appearing at 1122-1145 cm⁻¹ and 2919-2929 cm⁻¹ can be attributed to the vibrational absorption of CO and CH, indicating that hydroxyethyl cellulose and sodium polyacrylate have successfully crosslinked into a network. The absorption peak appearing at 1571-1635 cm⁻¹ is C=N, representing the linking group between the ionic liquid and the network, thus confirming the successful synthesis of the PILc gel membrane. The [BVIM]Br exhibits a characteristic absorption peak at 1058 cm⁻¹, which coincides with the boric acid-functionalized CB group. This characteristic absorption peak indicates that the gel film of this invention forms a cross-linked polymeric structure.

[0091] In addition, XRD analysis of the crystal structure was performed, and the results are shown in Figure B. The VL gel membrane exhibits obvious strong diffraction peaks at 32° and 33° 2θ. The [VIM]Br gel membrane also shows obvious 2θ peaks at 32° and 33°, but the intensity is significantly reduced, the baseline is uneven, and data spikes are quite noticeable. The synthesized [AVIM]Br gel membrane only shows a 32° diffraction peak at 2θ, without a 33° diffraction peak, and the peak intensity is very low. These results indicate that the gel membrane material of this invention cannot maintain its original crystal structure, has poor crystallinity, and contains a large amount of amorphous material, classifying it as a macromolecular polymer material. However, the synthesized [BVIM]Br gel membrane shows 2θ peaks at 32° and 33°, with a relative intensity nearly twice that of the [AVIM]Br gel membrane. Therefore, although the [BVIM]Br gel membrane is a macromolecular polymer material, the boric acid functionalization improves the crystallinity of the material. This hydrophobic crystalline structure facilitates the affinity and specific adsorption of hydrophobic components such as aflatoxin precursors and target compounds onto the gel membrane.

[0092] Example 3

[0093] The adsorption behavior of [AVIM]Br and [BVIM]Br gel membranes prepared in Example 1 on eight aflatoxins (AFs) (including AFB1, AFB2, AFG1 or AFG2) and their precursors (AT, AF, Z or OZ) was studied. The results are shown in the figure. Figure 7 In the diagram, A is the static adsorption diagram and B is the dynamic adsorption diagram. The specific operation is as follows:

[0094] The adsorption performance of the [AVIM]Br and [BVIM]Br gel membranes prepared in Example 1 for different concentrations of AFs and precursor compounds at different times was studied by adsorption isotherm and adsorption kinetic experiments.

[0095] For the adsorption isotherm experiment, 5.0 mg of [AVIM]Br and [BVIM]Br gel membranes were added to 1 mL of acetonitrile solutions of 8 AFs and precursors at different concentrations (10 µg·L⁻¹). -1 20 µg·L -1 50 µg·L -1 100 µg·L -1 200 µg·L -1 500 µg·L -1 1000 µg·L -1 and 2000 µg·L -1 The adsorbent was vortexed for 1 h to ensure full contact between the adsorbent and the target analyte. The maximum adsorption capacity of the four AFs on the [AVIM]Br gel membrane and the four AF precursors on the [BVIM]Br gel membrane adsorbent were studied.

[0096] For the adsorption kinetics experiment, 5.0 mg of [AVIM]Br and [BVIM]Br gel membranes were added to 1 mL of 8 AFs and precursor solutions (2000 μg·mL⁻¹). -1 The gels were vortexed to allow adsorption at different times (5 min, 10 min, 15 min, 20 min, 30 min, 60 min, 90 min, and 120 min). The equilibrium adsorption capacities of [AVIM]Br and [BVIM]Br gel membranes for eight AFs and precursor solutions were calculated. The maximum adsorption capacity Qe (µg·g) of [AVIM]Br and [BVIM]Br gel membranes was determined. -1 The following formula can be used for calculation:

[0097] (1)

[0098] In formula (1), the mass of the adsorbent is m (g), the volume of the solution is V (L), and the initial concentration of the target analyte is C0 (μg·L⁻¹). -1 At a certain moment (t) in the solution, the concentration of the target analyte is C. e (μg·L) -1 ), ignoring changes in solution volume.

[0099] Figure 7 Figure A illustrates the adsorption of the porous ionic liquid gel membrane material provided in Example 1 of this invention. The static equilibrium adsorption curves of [AVIM]Br and [BVIM]Br gel membranes for four AFs and four AF precursors at different initial concentrations are shown in Figure A. When the adsorbent dosage is 5.0 mg, the adsorption capacity of [AVIM]Br and [BVIM]Br gel membranes for AFs and precursors is within 0 μg·L⁻¹. -1 Up to 3000 μg·L -1 The concentration range gradually increased, reaching 2000 μg·L⁻¹. -1 Adsorption equilibrium was reached at this time. The calculated maximum experimental adsorption capacities of Z, OZ, AFB1, AFB2, AFG1, AFG2, AT, and AF were 195.3 µg·g⁻¹. -1 177.4 µg·g -1 178.9µg·g -1 183.2 µg·g -1 190.6 µg·g -1 187.4 µg·g -1 182.8 µg·g -1 and 179.5 µg·g -1Figure B shows the dynamic equilibrium adsorption curves of the [AVIM]Br and [BVIM]Br gel membranes for four AFs and their precursors at different adsorption times. The adsorption of the four AFs and their precursors by the [AVIM]Br and [BVIM]Br gel membranes is a stable and growing adsorption process, reaching adsorption equilibrium at 30 min. This may be attributed to the weak binding sites provided by the functionalized amino groups of [AVIM]Br and the functionalized phenylboronic acid of [BVIM]Br gel membrane, as well as the hydrogen bonding and electrostatic interactions between the AFs and their precursors. These results indicate that the [AVIM]Br and [BVIM]Br gel membranes have good adsorption performance for the four AFs and their precursors.

[0100] Furthermore, based on adsorption isotherm experiments, the adsorption mechanism of the [AVIM]Br and [BVIM]Br gel membranes prepared in Example 1 for eight AFs and precursors was investigated using the Langmuir and Freundlich models. Langmuir is based on the assumption that the target analyte is monolayer-covered on the outer surface of the adsorbent. The expression for Langmuir is:

[0101] (2)

[0102] In equation (2), Ce (µg·L) -1 ) is the equilibrium concentration, Qe (µg·g -1 ) is the equilibrium adsorption amount, Qs (µg·g -1 ) is the theoretical saturated adsorption capacity, and Kl is the Langmuir constant.

[0103] Freundlich is a multilayer adsorption process based on a non-homogeneous surface. The Freundlich equation is expressed as follows:

[0104] (3)

[0105] Where Kf and n are the Freundlich constant and affinity constant, respectively.

[0106] The Langmuir constants Kl for AFB1, AFB2, AFG1, AFG2, Z, OZ, AT, and AF were calculated as 2.4112E-4, 2.2689E-4, 2.3931E-4, 2.3324E-4, 1.9523E-4, 3.3886E-4, 3.2876E-4, and 2.6740E-4, respectively; Qs were calculated as 457.6613, 486.9987, 490.0614, 490.1554, 571.3027, 378.8751, 396.1706, and 433.6453, respectively; R 2 The Freundlich constants Kf for AFB1, AFB2, AFG1, AFG2, Z, OZ, AT, and AF were calculated to be 0.7809, 0.7907, 0.7810, 0.7887, 0.8193, 0.7302, 0.7344, and 0.7669, respectively; the n values ​​were calculated to be 0.3794, 0.3597, 0.4039, 0.3742, 0.3061, 0.5703, 0.5674, and 0.4272, respectively; R 2 The range is 0.9542 to 0.9627. The results show that the Langmuir isotherm has a better fitting coefficient than the Freundlich isotherm, therefore the Langmuir isotherm model is more suitable for describing this adsorption process than the Freundlich model, indicating that the adsorption process is mainly composed of monolayer adsorption on a homogeneous surface.

[0107] Further, based on adsorption kinetic experiments, the adsorption behavior of the [AVIM]Br and [BVIM]Br gel membranes prepared in Example 1 for eight AFs and precursors was investigated using pseudo-first-order and pseudo-second-order models. The pseudo-first-order model is based on the assumption that adsorption is controlled by a diffusion step, i.e., physisorption behavior. The expression of the pseudo-first-order model is:

[0108] (4)

[0109] The pseudo-second-order model assumes that the adsorption rate is determined by the square of the number of unoccupied adsorption vacancies on the adsorbent, and that the adsorption process is controlled by the chemisorption mechanism, i.e., chemisorption behavior, which involves electron sharing or electron transfer between the adsorbent and the adsorbate.

[0110] (5)

[0111] In equations (4) and (5), q e (µg·g -1 ) and q t (µg·g -1) represent the adsorption capacities at equilibrium and at time t, respectively, and k1 and k2 are the adsorption rate constants for pseudo-first-order and pseudo-second-order kinetics, respectively.

[0112] AFB1, AFB2, AFG1, AFG2, Z, OZ, AT and AF q e The values ​​are 185.5319, 190.1401, 197.9181, 198.2107, 206.1075, 185.0384, 192.5043, and 187.5899, respectively, and the pseudo-first-order constant k1 is calculated to be 0.0519, 0.0505, 0.0548, 0.0488, 0.0504, 0.0528, 0.0495, and 0.0499, respectively; R 2 The range is from 0.8735 to 0.9033; q of AFB1, AFB2, AFG1, AFG2, Z, OZ, AT and AF e The values ​​are 225.5716, 231.8302, 238.4069, 243.7846, 251.8247, 224.6492, 236.2435, and 221.5672, respectively. The pseudo-second-order constant k2 is calculated to be 2.3005 E⁻⁴, 2.1681 E⁻⁴, 2.3488 E⁻⁴, 1.9457 E⁻⁴, 1.9756 E⁻⁴, 2.3518 E⁻⁴, 2.0446 E⁻⁴, and 2.7124 E⁻⁴, respectively; R 2 The coefficient of determination ranges from 0.8223 to 0.8799. The pseudo-first-order model has a higher coefficient of determination than the pseudo-second-order model, indicating that the physical adsorption process is the main rate-controlling step in the interaction between the PILc gel membrane and the eight ATs in this invention, thus achieving high accuracy in the non-destructive detection of target substances, especially unstable AFs precursors.

[0113] Example 4

[0114] In this embodiment, the adsorption performance of the [AVIM]Br, [VIM]Br, and [BVIM]Br gel membranes prepared in Example 1 on eight AFs and their precursors was investigated. Specifically, 5.0 mg of each of the [AVIM]Br, [VIM]Br, and [BVIM]Br gel membranes was added to 1 mL of a mixed solution of the eight AFs and their precursors (2000 µg·mL⁻¹). -1 After vortexing for 30 min to reach adsorption equilibrium, an appropriate amount of supernatant was taken and filtered through a 0.22 µm filter membrane into a sample vial for further analysis by UHPLC-MS. The results are as follows: Figure 8As shown, the adsorption recoveries of the [VIM]Br gel membrane for the four AFs ranged from 61.8% to 66.4%, while the adsorption recoveries for the four AF precursors were slightly lower, ranging from 40.2% to 63.8%. This indicates that the [VIM]Br gel membrane relies on the electrostatic interaction of the imidazole ionic liquid itself to adsorb compounds containing π-electron cloud structures, such as AFs and their precursors. The adsorption recoveries of the [AVIM]Br gel membrane for the four AFs were as high as 91.7% to 99.4%, while the adsorption recoveries for the four AF precursors were only 29.5% to 56.1%. These adsorption recoveries demonstrate the adsorption capacity of the [AVIM]Br gel membrane for AFs, which contain coumarin-based structures. The [AVIM]Br gel membrane outperforms AF precursors, which contain anthraquinone-based structures. This can be explained by the fact that the specific adsorption sites of the [AVIM]Br gel membrane rely not only on the electrostatic interaction of imidazole but also on the hydrogen bond affinity between the functionalized amino groups and the 1,3-dione groups of AFs. In contrast, the [BVIM]Br gel membrane showed adsorption recoveries of only 30.8%–34.7% for the four AFs, but as high as 73.1%–99.4% for the four AF precursors. This indicates that the [BVIM]Br gel membrane has stronger adsorption performance for AF precursors. The specific adsorption sites rely not only on the electrostatic interaction of imidazole but also on the hydrogen bond affinity between the functionalized phenylboronic acid and the cis-dihydroxy groups of the AF precursors. This demonstrates that the PILc gel membranes formed by different functionalized ionic liquids bind to different target compounds and eliminate competitive interference.

[0115] Example 5

[0116] In this embodiment, the PILc material prepared in Example 1 was used as the sample pretreatment extraction adsorbent to investigate the adsorption performance of eight AFs and precursors. The study was conducted by varying several parameters, including the amount of PILc material, the type of elution solvent, the pH of the elution solution, the type of eluted ions, the elution time, and the elution volume. Specifically, the following parameters were investigated: the amount of [AVIM]Br and [BVIM]Br gel membranes (1–10 mg), the type of elution solvent (water H2O, methanol ME, ethanol EtOH, acetonitrile ACN, isopropanol IPA, ethylene glycol EG, diethylene glycol DEG, dichloromethane DCM, n-hexane n-Hex, ethyl acetate EA), the pH of the elution solution (1–14), the type of eluted ions (sodium bicarbonate NaHCO3, magnesium sulfate MgSO4, calcium carbonate CaCO3, potassium carbonate K2CO3, calcium chloride CaCl2, sodium chloride NaCl, potassium chloride KCl), the volume of the elution solvent (0.5–15 mL), and the elution time (0.5–120 mL). The effect of (min) on the extraction recovery of 8 AFs and precursors.

[0117] Experimental results are as follows Figure 9As shown, A represents the optimized adsorbent dosage, B represents the optimized elution solvent type, C represents the optimized solution pH, D represents the optimized elution ion type, E represents the optimized elution solvent volume, and F represents the optimized elution time. Specifically, as shown in Figure A, when the amount of [AVIM]Br and [BVIM]Br gel membranes used was 5.0 mg, the extraction recovery rates of the eight AFs and precursors tended to stabilize, reaching 70-100%. As shown in Figure B, when the elution solvent was diethylene glycol, the desorption recovery rates of the eight AFs and precursors tended to be uniform and stable. As shown in Figure C, when the pH was 7, i.e., without the addition of any acid or base reagents, the desorption recovery rates of the eight AFs and precursors reached their highest. As shown in Figure D, different eluting ions showed significant differences in elution efficiency for the eight AFs and precursors. When potassium chloride was used as the elution solvent, the elution recovery rate was more suitable because of the high difference in electronegativity between K and Cl. As shown in Figure E, when the elution volume was 2 mL, the elution recovery rates of the eight AFs and precursors were relatively ideal. As shown in Figure F, when the elution time was 60 min, the elution recovery rates of the eight AFs and precursors could achieve slow release and tend to stabilize.

[0118] In summary, the PILc material of the present invention has the advantages of low material consumption, simple operation, and adjustable adsorption target as an extraction adsorbent for sample pretreatment. Therefore, it can be seen that the gel membrane material of the present invention has a very broad application prospect.

[0119] Example 6

[0120] In this embodiment, evaluating the feasibility of combining PILc materials with rapid evaporation ionization mass spectrometry (REIMS) is of great significance for assessing the excellent performance of PILc adsorbent materials as key components for rapid detection and improving the early warning application potential for the specific identification of unstable structural compounds such as AFs precursors. Figure 10 As shown, 1 x 1 cm of each of the VL, [AVIM]Br, [VIM]Br, and [BVIM]Br gel membrane adsorbents prepared in the comparative example and Example 1 were used. 2After being added to 1 mL of acetonitrile extraction solution from soybean soy sauce for thorough adsorption, the PILc exhibited a sponge-like appearance after adsorption equilibrium. When directly cut at high temperature with a scalpel, the VL gel membrane could only be cut 3 times, and the data deviation was significant. [VIM]Br increased the number of cuts, but the data quality did not improve. The [AVIM]Br and [BVIM]Br gel membranes could be repeatedly cut multiple times with stable data signals. This ensures the stable and accurate detection of trace aflatoxin precursors on the gel membrane adsorbent. Therefore, the PILc material of this invention maintains repeatable cutting performance under rapid evaporation ionization conditions, ensuring the accuracy of non-destructive detection of trace aflatoxin precursors in fermented foods. Its feasibility for coupling with REIMS is good, thus achieving a technological breakthrough by combining in-situ ionization technology of food samples with an early warning mode for aflatoxin.

[0121] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A porous ionic liquid gel membrane material, characterized in that, It is a loose, porous three-dimensional network structure formed by functional monomers of repeating structural units and a membrane. The functional monomers are ionic liquids formed by imidazole derivatives. The membrane is formed by cross-linking hydroxyethyl cellulose and sodium polyacrylate. The repeating structural units are connected by electrostatic interaction between nitrogen cations formed by cross-linking ionic liquid with hydroxyethyl cellulose and oxygen anions formed by sodium polyacrylate.

2. The porous ionic liquid gel membrane material according to claim 1, characterized in that, The porous ionic liquid gel membrane material exhibits crystalline diffraction peaks at 2θ positions (32° and 33°) in X-ray powder diffraction data; the average specific surface area of ​​the porous ionic liquid gel membrane material is 1.25–2.52 m². 2 ·g −1 The average pore size is 30~55 nm.

3. The porous ionic liquid gel membrane material according to claim 1, characterized in that, The functional monomer is selected from one or more combinations of ionic liquids formed from the following imidazole derivatives: the imidazole derivative is 1-vinylimidazole, and the ionic liquid formed from the imidazole derivative has the structure shown below: wherein, R is C2NH6Br - C4H6Br - Or C7BH8O2Br, 。 4. The porous ionic liquid gel membrane material according to claim 1, characterized in that, The hydroxyethyl cellulose is a nonionic cellulose ether with the structure shown below, and its chemical formula is (C2H6O2). n Degree of polymerization n ranges from 600 to 800. ; The sodium polyacrylate is a water-soluble linear polymer with the following structure and chemical formula (C3H3O2Na). n Molecular weight ≥ 3x10 7 The range of n is 1x10. 6 ~5x10 6 , 。 5. A method for preparing a porous ionic liquid gel membrane material according to any one of claims 1 to 4, characterized in that, The preparation method includes the following steps. (1) The imidazole derivative is made into an ionic liquid as a functional monomer, and the imidazole derivative and the functional monomer are as described above; (2) The crosslinking agent and the functional monomer prepared above are preheated and stirred, and then hydroxyethyl cellulose and aprotic polar solvent are added to react to obtain a homogeneous solution. After the reaction is completed, the solution is cooled to room temperature, and an aqueous solution of sodium polyacrylate with the same volume as the homogeneous solution obtained above is added. The mixture is stirred and mixed repeatedly to form a film until a large amount of powder precipitates. The hydroxyethyl cellulose and sodium polyacrylate are as described above. (3) Collect the powder and place it on a glass plate. After processing and vacuum drying, the gel membrane material is obtained.

6. The preparation method according to claim 5, characterized in that, In step (1), the ionic liquid is prepared as follows: The imidazole derivative, crosslinking agent, and desiccant were mechanically stirred in an organic solvent to obtain a mixture. The mixture was then heated in an oil bath under nitrogen atmosphere. After the reaction was completed, the mixture was cooled to room temperature, and the precipitate was collected or removed to obtain an ionic liquid.

7. The preparation method according to claim 6, characterized in that, The crosslinking agent that reacts with the imidazole derivative is 2-bromoethylamine hydrobromide, 4-bromo-1-butene, or 4-(bromomethyl)phenylboronic acid; the mass ratio of the imidazole derivative to the crosslinking agent is 1:(1~3).

8. The preparation method according to claim 5, characterized in that, In step (2), the crosslinking agent reacting with hydroxyethyl cellulose is a halogenated hydrocarbon compound containing an epoxy structure, which is epichlorohydrin, epibromopropane, methyl epichlorohydrin, bromopropane, or 1,2-epoxy-4-chlorocyclohexane.

9. The preparation method according to claim 8, characterized in that, The mass ratio of the crosslinking agent, functional monomer and hydroxyethyl cellulose is 1:(1~3):(0.1~1).

10. The use of a porous ionic liquid gel membrane material according to any one of claims 1 to 4 or a porous ionic liquid gel membrane material obtained by any one of claims 5 to 9 in resisting competitive interference from aflatoxin or in preparing products for enriching aflatoxin precursors; The aflatoxin is at least one of aflatoxin B1, aflatoxin B2, aflatoxin G1, or aflatoxin G2. The aflatoxin precursor is at least one of Averantin, Averufin, trachomatis, or O-methyltrachomatis.